Prospective comparative study of dose dense neo-adjuvant chemotherapy followed by chemo-radiation and definitive chemo-radiation alone in stage IB2-IVA cervical cancer - Karpurmath, Shashidhar V.; Nimma, Shravan; Narayanan, Geeta S.; Nandennannavar, Manjunath I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The standard of care for locally advanced cervical cancer is chemo-radiation. Role of neo-adjuvant chemotherapy not clear yet. Dose dense, short-term neo-adjuvant chemotherapy with early initiation of radiotherapy has shown survival benefit but randomised trials not available yet. Hence this study was done for feasibility of neo-adjuvant chemotherapy and for its comparison with the standard chemo-radiation. Methods: Cervical cancer patients not randomly assigned into two arms. Arm A received 3 cycles NACT of paclitaxel and carboplatin weekly. All patients of arm A after NACT and arm B received EBRT on linear accelerator for a dose of 4500-5000cGy in 23-25 fractions with concurrent cisplatin 40mg/m2 followed by 3 applications of HDR intracavitary brachytherapy of 700 or 800cGy respectively. All patients were assessed clinically and radiologically with MRI after completion of CTRT and at follow up of 6 weeks. Results: A total of 15 patients treated in each arm. Stage IIB and IIIB constituted 93% of the patients, well matched in both the arms. The CR rate at follow up of 6 weeks after NACT was 73% compared to only 46.7% in arm B. Neutropenia of grade 3 were seen equally in both the arms and grade 2 neutropenia was seen in about 60% patients in arm A compared to only 20% patients in arm B which was manageable without growth factors. Conclusions: Dose dense neo-adjuvant chemotherapy is a feasible and effective option in treating cancer cervix.